DUKUNGAN SOSIAL TERHADAP ADAPTABILITAS WANITA KARIR - Amanda Meiliani Putri; Kamila Fatimah Shaliha; Firda Sofa Az-Zahro; Rahma Tya Antari; Rama Wijaya Abdul Rozak (Triwikrama: Jurnal Ilmu Sosial, 2025)
The purpose of this study is to describe whether social support has a major influence on the adaptability of career women and how the role of social support is a predictor of career women's adaptability. The sampling technique was purposive sampling with a sample size of 50 career women. The data collection technique used in this study was a questionnaire. This study uses the Career Adapt-Abilities Scale - Short Form (CAAS-SF) measuring instrument. The results of this study indicate that Social Support for Career Women's Adaptability has a percentage of 80%, which means that social support is very influential on career adaptability. They feel that social support also has a very significant influence on their career adaptability.